Optimum land allocation under different crops employing TLBO technique and assessment of land and water productivity - UPADHYAYA, ASHRUTI; UPADHYAYA, ASHUTOSH; AHMED3, AKRAM; JEET, PAWAN (Journal of Soil and Water Conservation, 2022)
In India, agriculture is not a profitable venture because lot of risks and uncertainties are involved in it. Indiscriminate and unscrupulous use of inputs/resources and absence of scientific planning leads to increase in cost of inputs and reduction in income from output or net return. Optimization techniques have been employed since last many decades to solve the agricultural problems and have proved capable in providing optimal solutions. A study was undertaken in Bhagwanpur distributary of Vaishali Branch Canal in Gandak Canal Command of Bihar state, India to optimally allocate land under different crops (rice and maize in kharif, wheat, lentil, potato in rabi and green gram in summer) by employing Teaching Learning Based Optimization (TLBO) method in such a manner that maximizes net returns considering different proportions of canal water and ground water used at three different affinity levels. Maximum net return of Rs 37.07 crore at 10% affinity level; Rs 33.11 crore at 20% affinity level; and Rs 29.16 crore at 30% affinity level is obtained. It followed a decreasing trend when affinity levels increased from 10% to 30%. Decrease in maximum land productivity (from 4415.5 Rs./ha to 3914.8 Rs./ha) and maximum water productivity (from 52.58 Rs./m3 to 33.50 Rs./m3) on increase in affinity level from 10% to 30% is observed. The results are useful in suggesting an optimum land allocation plan under different crops that gives maximum net return, land productivity and water productivity under different canal and ground water use scenarios and affinity levels.